Soil properties and shallot yield responses to different salinity levels - Syamsiyah, Jauhari; Rahayu, Rahayu; Binafsihi, Wily (Universitas Sebelas Maret, 2020)
Successful management of saline water could have significant potential for agricultural development in many areas, particularly in freshwater-scarce regions. To date, the effect of salinity on shallot (Allium Cepa L.) yield and growth parameters has not been studied in detail specifically for local varieties cultivated in Inceptisols. Therefore, the present study was designed to evaluate the effects of different levels of irrigation-water salinity (0, 1, 2, and 3 dSm-1) on soil chemical properties, the growth, and yield of local shallot varieties. The experiment was conducted in pots using a randomized plot design with two factors and three replications. The results showed that increases in salinity level affected increases soil pH, exchangeable Na percentages, and plant height growth. Nevertheless, bulb number and weight, soil exchangeable Ca and Mg, soil organic carbon, and sodium adsorption ratio (SAR) was not significantly affected. The findings of the present study suggest that the local varieties—Brebes and Purbalingga—with irrigated salinity levels up to 3 dSm-1can be tolerated for shallot cultivation in Inceptisols.